Evolution of local scour downstream of Type A PK weir in non-cohesive sediments - Lantz Wyatt D.; Crookston Brian M.; Palermo Michele (Journal of Hydrology and Hydromechanics, 2022)
A large-scale piano key weir laboratory study was conducted to investigate the evolution of the scour process occurring in the downstream basin for two non-cohesive granular bed materials, including the analysis of scour-hole geometry and patterns at equilibrium. It was observed that hydraulic conditions, particularly tailwater level, significantly affect the scour mechanisms and equilibrium morphology, eventually resulting in scour depths that exceeded the weir height. Unprecedented insights on the scour dynamics are also provided, along with tools to estimate the time evolution and maximum scour depth, its location in the streamwise direction, and the maximum scour length.